A teleological approach to the wicked problem of managing Utría national park (2017)
Utría National Park is a remote biodiversity hotspot in Colombia. It encompasses ancestral territories of the Embera indigenous peoples and borders territories of Afro-descendant communities in El Valle. We explore environmental value conflicts regarding the use of the park, describing them as a Wicked Problem that has no clear solution. Juxtaposing how the territory is perceived by different communities, we employ Faber et al.'s heuristic of the three tele of living nature to search for deficiency in the third telos, service, which we take to be symptomatic of Wicked Problems. Based on field data encoded using the three-tele heuristic, concerning how the respective communities would like to use the park area, we identify deficiencies in the third telos and develop recommendations regarding how these might be addressed.